Promotion Campaigns in the Maritime Sector and the Attitude of Young People towards a Career at Sea - Zaar, Staffan; Hammarstedt, Kaisa (My University, 2012)
The maritime sector considers itself to be unknown to the public and the interest in a career at sea seems to decrease worldwide. Therefore, a few promotion campaigns intending to increase the knowledge of the maritime sector and its career opportunities have been carried out. These campaigns form the background to this thesis having the following aim: 1. to map promotion campaigns intending to attract young people to a career at sea or within the maritime sector, carried out mainly in Sweden but also in Denmark, Estonia, Finland, Germany, Latvia, Lithuania, Norway and Poland, 2. to gather information on attitudes and career choices of young people in Sweden and compare these findings to the career choices offered by the maritime cluster and to the promotion campaigns carried out by the maritime sector and 3. to study, with the help of a survey, whether students in Sweden have recognized any promotion campaign carried out in Sweden in order to attract young people to a seagoing career and what attitudes they have towards a career at sea or within the maritime sector. To learn what measures have been taken to promote the maritime sector websites of maritime academies and of promotion campaigns have been analysed. It was found that the campaigns in Denmark, Finland, Norway and Sweden were organized in similar ways. Different actors within the maritime sector supported the campaigns and the websites constituted a central part of the campaigns. Denmark and Norway distinguished themselves from Sweden and Finland by having more extensive websites and by putting focus on the career opportunities offered within the shore based part of the maritime sector as well as on a seagoing career. Further it was found that different actors within the Polish maritime sector had established a co-operation with the purpose of carrying out joint promotion activities. In Estonia, Latvia and Lithuania no co-operation between different parties could be found. Instead open days were arranged by the maritime academies which also participated in student and educational fairs. In Germany recruitment activities were carried out by the German Shipowners’ Association. From the Baltic States no information was retrieved regarding the success of the promotion activities, but the campaigns carried out in the Nordic countries, Germany and Poland were all considered to be successful. When promoting the career opportunities offered within the maritime sector the possibility to travel and to work internationally is often highlighted, but the Swedish study Youths with Attitude shows that the possibility to make international contacts is one of the least important aspects of an employment. Instead the possibility to work near home and to be able to combine work and family life is more relevant. The result of the questionnaire survey corresponds to the Youths with Attitude study by showing that the periods away from home were the most negative aspect of a seagoing career. Yet almost half of the respondents could see themselves working at sea. With these findings in mind focus should, when promoting a career at sea, be put on the possibility to work ashore within the maritime sector after a few years at sea.
Keywords: Transport; Farkostteknik; Transport; Vehicle Engineering